Open Comparison Study between Augmentin and Ampicillin-Chloramphenicol in the Treatment of Bronchopneumonia in Children - M. Hardjono Abdoerrachman (Indonesian Pediatric Society Publishing House, 2018)
Sixty children under 2 years of age suffering from bronchopneumonia were evaluated for the effectiveness of the treatment. The first group consisted of 30 patients was treated with a single drug, i.e. , Augmentin (amoxycillin and clavulanic acid) as a study group. The second group was treated with a combination of ampicillin and chloramphenicol as a control group. The two groups showed good clinical response to the the given treatment. Clinical signs and symptoms of bronchopneumonia disappeared within the similar period in both groups, including decrease of fever, disappearance of dyspnea, and diminution or disappearance of rales. The clinical effectiveness in this study, as measured by the disappearance of clinical signs and symptoms, was considered to have a success rate of 82.1% in the study group and 72.2% in control group.